Stanje trga nepremičnin v Sloveniji - Pahulje, Klemen (Gradbeni vestnik, 2019)
Socio-economic development and the absence of long-term and consistent housing policy in the management and maintenance of multi dwelling buildings result in inadequate material state of Slovenia's housing fund. The challenge is to overcome the main obstacles impending the renovation of the housing stock. There is a need for legislative arrangements of multi-dwelling building management (legislative function), creating conditions for the financial fitness of renovating multi-dwelling buildings (economic function) and strengthening of responsibility towards joint-ownership, social cohesion and awareness among the dwelling owners (social function). Considering the social specifics, it is necessary to actively approach the integration of instruments or other measures for effective management and maintenance of multi dwelling buildings in Slovenia and take into account the good practices of other countries with a long tradition in this field.
Keywords: housing fund; inženirska ekologija; maintenance; management; multi-dwelling buildings; stanovanjski fond; upravljanje večstanovanjskih stavb; vzdrževanje večstanovanjskih stavb